Euclid’s Algorithm and its Role in Solving Modular Multiplicative Inverse - Kandel, Dev Raj (Kaumodaki: Journal of Multidisciplinary Studies, 2024)
In this article, the prime motivation is to demonstrate how calculating modular multiplicative inverse can be simplified computationally with the help of Euclid’s algorithm, which is usually attributed to finding the Greatest Common Divisor.